The DNA damage sensor ATM kinase interacts with the p53 mRNA and guides the DNA damage response pathway - Karakostis, Konstantinos; Malbert-Colas, Laurence; Thermou, Aikaterini; Vojtesek, Borek; Fåhraeus, Robin (Molecular cancer, 2024)
BACKGROUND: The ATM kinase constitutes a master regulatory hub of DNA damage and activates the p53 response pathway by phosphorylating the MDM2 protein, which develops an affinity for the p53 mRNA secondary structure. Disruption of this interaction prevents the activation of the nascent p53. The link of the MDM2 protein-p53 mRNA interaction with the upstream DNA damage sensor ATM kinase and the role of the p53 mRNA in the DNA damage sensing mechanism, are still highly anticipated. METHODS: The proximity ligation assay (PLA) has been extensively used to reveal the sub-cellular localisation of the protein-mRNA and protein-protein interactions. ELISA and co-immunoprecipitation confirmed the interactions in vitro and in cells. RESULTS: This study provides a novel mechanism whereby the p53 mRNA interacts with the ATM kinase enzyme and shows that the L22L synonymous mutant, known to alter the secondary structure of the p53 mRNA, prevents the interaction. The relevant mechanistic roles in the DNA Damage Sensing pathway, which is linked to downstream DNA damage response, are explored. Following DNA damage (double-stranded DNA breaks activating ATM), activated MDMX protein competes the ATM-p53 mRNA interaction and prevents the association of the p53 mRNA with NBS1 (MRN complex). These data also reveal the binding domains and the phosphorylation events on ATM that regulate the interaction and the trafficking of the complex to the cytoplasm. CONCLUSION: The presented model shows a novel interaction of ATM with the p53 mRNA and describes the link between DNA Damage Sensing with the downstream p53 activation pathways; supporting the rising functional implications of synonymous mutations altering secondary mRNA structures.
Keywords: nádorový supresorový protein p53; DNA Damage; polynukleotid-5'-hydroxylkinasa; Genotoxic stress; poškození DNA; Synonymous mutations; ATM protein; Polynucleotide 5'-Hydroxyl-Kinase; protoonkogenní proteiny c-mdm2; MRN complex; Tumor Suppressor Protein p53; Proto-Oncogene Proteins c-mdm2; MDM2; Humans; oprava DNA; Precision medicine; Ataxia Telangiectasia Mutated Proteins; DNA Damage Sensing; DNA Repair; lidé; RNA secondary structure